Turism Economy and Governance. The Case of the Municipality of San Rafael in Colombia - KIRADJIEVA, Julia; ÁLVAREZ, Liliana LOTERO; BOTERO MONTOYA, Luis Horacio (Journal of Environmental Management and Tourism, 2021)
This article explores tourism from the standpoint of circular economy and governance concepts targeting the municipality of San Rafael in the Colombian region of Antioquia. The methodological approach is qualitative with a purposive search of primary and secondary sources. Furthermore, the analysis is based on contrasting and comparing postulations of the World Tourism Organization (WTO), the Sustainable Development Goals (SDGs), and the Colombian normativity. The study’s conclusion points out the importance of reframing the municipality’s tourism model towards a sustainability culture. To this end, the implementation of the circular economy approach and new models of governance prove to be not only an imperative, but a necessity.